2006
DOI: 10.1002/lsm.20279
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal effects of diode laser on Streptococcus mutans after irradiation through different thickness of dentin

Abstract: Background and Objectives: A reliable method to eradicate the bacteria of residual carious dentin has not yet been developed. The aim of this study was to evaluate the antibacterial effect of a diode laser on Streptococcus mutans through different thickness (500, 1,000, and 2,000 mm) of human dentin. The thermal effect of laser irradiation was also investigated. Study Design/Materials and Methods: Dentin specimens were inoculated with 2 ml of S. mutans on one side and irradiated by a diode laser on the other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
1
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 32 publications
5
33
1
9
Order By: Relevance
“…3 Temperature change of plate after laser irradiation Almost no increase in temperature of anhydrous quartz at 1.67m or 2.94m, but temperature of dentin plates increased to more than 90°C at both wavelengths. provide sufficient sterility for caries, periodontal disease or infected root canals 2,[4][5][6][8][9][10]13,18) . In this study, S. mutans was selected as the target from the perspective of prevention of secondary caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Temperature change of plate after laser irradiation Almost no increase in temperature of anhydrous quartz at 1.67m or 2.94m, but temperature of dentin plates increased to more than 90°C at both wavelengths. provide sufficient sterility for caries, periodontal disease or infected root canals 2,[4][5][6][8][9][10]13,18) . In this study, S. mutans was selected as the target from the perspective of prevention of secondary caries.…”
Section: Discussionmentioning
confidence: 99%
“…Lasers have been used clinically in dental practice for various purposes, including tooth cutting, washing in root canals, scaling, and pain relief in soft tissues 14,15) ; and many studies have reported the bactericidal effects of lasers. 2,[4][5][6][8][9][10]13,18) However, lasers have different properties depending on wavelength; for example, the Nd:YAG laser has high tissue permeability and is able to affect deep tissue, whereas the Er:YAG laser has good absorption properties in water and acts on the surface of tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many methods have been established to eliminate S. mutans from the oral cavity [1,2]. One such approach is photodynamic therapy [3][4][5]. A series of studies have demonstrated the photodynamic inactivation of bacteria by the exogenous application of a photosensitizer such as methylene blue or toluidine blue [4].…”
Section: Introductionmentioning
confidence: 99%
“…22 Lazerlerin antibakteriyel etkisi, lazer enerjisi, absorpsiyon özellikleri, hücrenin hacmi ve su içeriği, bakterilerin dentin tübüllerin-deki hareketi gibi birçok faktöre bağlıdır. 23,24 Çalış-malarda, farklı lazer tiplerinin farklı bakterilere karşı antibakteriyel etkilerinin olduğu gösterilmiş-tir. 10,23,25 Lazerlerin kavite dezenfeksiyonunda olumlu etkilerine rağmen, adezif sistemlerin dentine bağlanmasında negatif etkilerinin olduğunu belirten çalışmalar mevcuttur.…”
unclassified
“…23,24 Çalış-malarda, farklı lazer tiplerinin farklı bakterilere karşı antibakteriyel etkilerinin olduğu gösterilmiş-tir. 10,23,25 Lazerlerin kavite dezenfeksiyonunda olumlu etkilerine rağmen, adezif sistemlerin dentine bağlanmasında negatif etkilerinin olduğunu belirten çalışmalar mevcuttur. [26][27][28] Araştırmacılar, bu olumsuz etkiyi lazerlerin kollajen fibril ağlarını denatüre etmesine bağlamışlardır.…”
unclassified